Pelatihan dan Pendampingan Kecakapan Hidup Berorientasi Keluarga Maslahat bagi Muslimat Nahdlatul Ulama Sukabakti Sodonghilir Tasikmalaya - Hinayatulohi, Ahmad; Sopwandin, Iwan; Baits, Abdul; Mubarokah, Indahilma (CV. Biha Cendekia, 2025)
Family plays a strategic role in character formation, social resilience, and the development of human resources, particularly in rural communities. However, limited family life skills, such as conflict management, parenting practices, and adaptation to digital challenges, may weaken family resilience. This Community Service Program aimed to enhance understanding of the concept of maslahah family and to develop family life skills based on Islamic values through training and mentoring activities at Majlis Taklim Nurul Hilal, Sukabakti Village, Sodonghilir District, Tasikmalaya Regency. The program employed a participatory action approach using training and mentoring methods, involving families who are members of the majlis taklim as the primary participants. The activities were conducted in three stages: preparation, implementation, and evaluation. The results indicated an improvement in participants’ understanding of maslahah family values, family communication skills, conflict management strategies, and awareness of adaptive parenting in the digital era. Furthermore, the program strengthened the role of the majlis taklim as a community-based center for family empowerment rooted in religious values and local wisdom. This initiative contributed positively to strengthening family resilience and improving the quality of social life in rural communities.